Harrison's manual of oncology - Chabner, Bruce; Lynch, Thomas J. (Thomas James) 1960-; Longo, Dan L. (Dan Louis) 1949-; Harrison, Tinsley Randolph 1900-1978 (McGraw-Hill Education Medical, 2014)
Offers an overview of the medications and approaches used in cancer care. This book features numerous tables and succinct, outline-style text that puts important information at your fingertips.